From Kabul to Cairo and Back Again: The Afghan Women’s Movement and Early 20th Century Transregional Transformations - Marya Hannun (Genre & Histoire)
When Afghan women are mentioned in the story of the country’s independence, it is most often in relationship to men, as either objects of King Aman Allah Khan’s Islamic reforms (r.1919-1929) or else as the locus of backlash against these reforms. This narrative reverberates to this day in discourses about “saving” Afghan women, which paints a picture of a conflict-prone society where women are reduced to a monolithic, voiceless category. Yet locating women in this historical period tells a more nuanced and far-reaching story. This article traces Afghan women and the discourses around them across archives from Egypt to India in order to demonstrate how the nascent women’s movement that emerged in early twentieth-century Afghanistan was part of a broader transregional dialogue in which elite women were key actors. The “Balkans-to-Bengal complex” identified by Shahab Ahmad has galvanized scholars of the early modern Islamic world to think through new spatial frameworks, and the Ottoman-Indian nexus continues to provide a useful frame of reference for understanding women’s reform between the two World Wars. I discuss methodological approaches to locating women and their voices in male-dominated archives, as well as the theoretical insights provided by this endeavor. In so doing, I challenge accounts that isolate Afghanistan and dismiss women’s participation during this period as instrumental and ephemeral.